OP033 The effect of tofacitinib on serum lipids and cardiovascular safety in patients with ulcerative colitis: results from the tofacitinib ulcerative colitis clinical programme. (16th January 2018) - Sands, B E; Taub, P R; Feagan, B G; Armuzzi, A; Friedman, G S; Moscariello, M; Lawendy, N; Pedersen, R D; Chan, G; Nduaka, C I; Quirk, D; Salese, L; et al.
Abstract: Background: Tofacitinib is an oral, small-molecule Janus kinase inhibitor that is being investigated for ulcerative colitis (UC). We describe baseline (BL) cardiovascular (CV) risk, the effect of tofacitinib treatment on lipid concentrations, and incidence rates (IRs; patients with events per 100 patient-years) of major adverse CV events (MACE) in patients enrolled in the UC global development programme. Methods: Analyses were performed for patients in three placebo-controlled induction studies (Ind), a 52-week placebo-controlled maintenance study (Main) and an ongoing, open-label, long-term extension (LTE) study ( N = 1157). Lipid concentrations were assessed at pre-induction BL and up to Week 61 for responders to tofacitinib 10 mg twice daily (BID) in Ind who were randomised to tofacitinib 5 or 10 mg BID or placebo in Main. IRs and confidence intervals (CI) for MACE were calculated (follow-up to December 2016), including patients with ≥1 event per 100 patient-years of exposure. The distribution of CV risk factors and Reynolds Risk Score (RRS) was determined for male patients ≤45 and >45 years and female patients ≤55 and >55 years. Results: Mean pt age was 41.3 years. At BL, RRS was ≥10% in 24.4% of males >45 years and 6.4% of females >55 years. Most patients did not require lipid-lowering medication (Table). Dose-dependent increases in total cholesterol (TC), high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c) and triglycerides were observed, which remained stable up to Week 61 in Main patients assigned to placebo, tofacitinib 5 mg BID and 10 mg BID; LDL-c:HDL-c and TC:HDL-c ratios were unchanged. In the overall clinical programme, four MACE events were reported (IR 0.24; 95% CI 0.07, 0.62; males 3/668 [0.4%]; females 1/475 [0.2%]): one haemorrhagic stroke, one aortic dissection, one acute coronary syndrome, one myocardial infarction. The aortic dissection resulted in death (patient had 1 CV risk factor). The haemorrhagic stroke led to permanent tofacitinib discontinuation. The myocardial infarction and acute coronary syndrome events led to temporary tofacitinib discontinuation (patients completed the study). These three patients had ≥4 CV risk factors at BL, including hyperlipidaemia. Conclusions: Tofacitinib treatment was associated with increases in TC, HDL-c and LDL-c in patients with UC, while LDL-c:HDL-c and TC:HDL-c ratios were unaffected. These results are similar to those reported for rheumatoid arthritis (RA). MACE events were infrequent, with rates similar to those reported in the tofacitinib RA programme and for other UC agents; three of four patients had multiple CV risk factors.